Peran Akuntansi Zakat terhadap Transparansi dan Akuntabilitas di Lembaga Amil Zakat Muhammadiyah Kota Parepare - Nurhamida; Idris, Mahsyar; Semaun, Syahriyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research employs a qualitative, descriptive research approach. The primary data sources consist of employees from LAZISMU Parepare City and representatives of the muzakki, while secondary data include necessary documents from LAZISMU Parepare City. The researcher, assisted by interview guides, documents, and a mobile phone for documentation and recording processes, acts as the research instrument. The research findings indicate that (1) LAZISMU Parepare City has been following PSAK No. 109 in its accounting processes as instructed by LAZISMU Central. Despite not yet adopting the latest revisions of PSAK No. 109 in its financial reporting process, LAZISMU Parepare City is committed to implementing the revised PSAK No. 109 in the near future. (2) In efforts to enhance transparency and accountability, LAZISMU has reported its financial statements to internal stakeholders, including muzakki who are civil servants, and has undergone audit processes by both external auditors and the Ministry of Religious Affairs. However, LAZISMU Parepare City has not reported its financial statements to external parties, particularly the wider community and non-civil servant muzakki. (3) The compliance of LAZISMU Parepare City's financial statements with Sharia principles outlined in Surah Al-Baqarah: 282 meets the criteria, as confirmed by the Sharia compliance audit conducted by the Ministry of Religious Affairs. Nevertheless, certain points in the process need to be adjusted to align with the current conditions of Parepare City.